SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN KARET (Havea brasiliensis Muell. Arg) PADA TANAH GAMBUT YANG DITUMBUHI DAN TIDAK DITUMBUHI Mucuna bracteata - Ajunfadil Aristio; Wardati Wardati; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
One effort to improve the chemical properties of peat soils and the growth of rubber trees is by planting a legume cover crop Mucuna bracteata. The research aims to determine the chemical properties of the soil and the growth of rubber trees in peat soils without overgrown Mucuna bracteata with peat soils ex overgrown Mucuna bracteata and peat soil that overgrown Mucuna bracteata. The research was conducted in January – March 2016 in peat land at social plantation areal of PT. RAPP Teluk Meranti. The research was conducted by survey method where the determination of location specified by Stratified Random Sampling method and the determination of sample point specified by Simple Random Sampling method. The results showed that peat soil which is overground Mucuna bracteata has a pH value, C-organic, N-total, P-total, KTK, KB and the growth of rubber trees better than peat soils ex overgrown Mucuna bracteata and peat soils withouth overgrown Mucuna bracteata.Keywords : Peat soil, chemical properties, Mucuna bracteata, rubber.